Nyāyapraveśakaśāstram - Dignāga (Motilāla Banārasīdāsa ; Śrī Siddhibhuvanamanohara Jaina Ṭrasṭa ; Śrī Jaina Ātmānanda Sabhā, 2009)
Treatise on Buddhist logic with two commentaries; includes Tibetan translation of (Narthang and Peking edition) as appendices.